2003
DOI: 10.1111/1467-8624.00584
|View full text |Cite
|
Sign up to set email alerts
|

Child Care Quality Matters: How Conclusions May Vary With Context

Abstract: Three studies examined associations between early child care and child outcomes among families different from those in the National Institute of Child Health and Human Development (NICHD) Early Child Care Research Network study. Results suggest that quality is an important influence on children's development and may be an important moderator of the amount of time in care. Thus, the generalizability of the NICHD findings may hinge on the context in which those results were obtained. These studies, conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
2
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(167 citation statements)
references
References 19 publications
4
151
2
10
Order By: Relevance
“…In within-country studies, the range of these structural indicators may be limited because of government legislations, and therefore across-country studies are expected to include a wider range of group size and child-caregiver ratios. Previous cross-country studies that encompassed a wider range of quality than typically seen in one country (Love et al 2003) have demonstrated that this approach can uncover stronger associations than is possible in within-country studies. Drawing on earlier work (Phillipsen et al 1997), our hypothesis is that process quality will be negatively associated with group size and child-caregiver ratio; that is, it will be higher when group sizes are smaller and/or when fewer children are cared for by one caregiver.…”
Section: Process Quality and Structural Featuresmentioning
confidence: 99%
“…In within-country studies, the range of these structural indicators may be limited because of government legislations, and therefore across-country studies are expected to include a wider range of group size and child-caregiver ratios. Previous cross-country studies that encompassed a wider range of quality than typically seen in one country (Love et al 2003) have demonstrated that this approach can uncover stronger associations than is possible in within-country studies. Drawing on earlier work (Phillipsen et al 1997), our hypothesis is that process quality will be negatively associated with group size and child-caregiver ratio; that is, it will be higher when group sizes are smaller and/or when fewer children are cared for by one caregiver.…”
Section: Process Quality and Structural Featuresmentioning
confidence: 99%
“…Controlling for concurrent time in care also reduces the possibility that the association between child care hours and externalizing behavior is caused by the child (because children with more behavior problems are left in child care for longer hours every day or for more days of the week, for example) rather than by child care. This is a difficult proposition to test in the real world because children who spend a lot of time in child care early on tend to do so at later ages as well (Love et al, 2003;NICHD ECCRN 2003). Nevertheless, if the association between the amount of time spent in care at time 1 and externalizing behavior at time 2 is still significant after the amount of time spent in care at time 2 is controlled, this would be consistent with the causal argument that child care hours is linked with externalizing behavior.…”
Section: Five Causal Propositionsmentioning
confidence: 99%
“…High levels of turnover prevent caregivers from acquiring experience, and keep children from forming stable, secure attachments (Love et al 2003;Raikes 1993;Scarr et al 1994). A long literature in child development and psychology has shown that the capacity of very young children to form secure attachments is critical for their development (in particular, socio-emotional development), and that children who do not form secure attachments with adults have worse outcomes in school, and higher levels of clinical depression and criminal activity in adulthood (Ainsworth and Bell 1970;Bowlby 1969 benefits to policies that seek to reduce turnover among caregivers in child care.…”
Section: Resultsmentioning
confidence: 99%